On the impact of security vulnerabilities in the npm and RubyGems dependency networks - Zerouali, Ahmed; Mens, Tom; Decan, Alexandre; De Roover, Coen (Empirical software engineering : an international journal, 2022)
The increasing interest in open source software has led to the emergence of large language-specific package distributions of reusable software libraries, such as npm and RubyGems. These software packages can be subject to vulnerabilities that may expose dependent packages through explicitly declared dependencies. Using Snyk’s vulnerability database, this article empirically studies vulnerabilities affecting npm and RubyGems packages. We analyse how and when these vulnerabilities are disclosed and fixed, and how their prevalence changes over time. We also analyse how vulnerable packages expose their direct and indirect dependents to vulnerabilities. We distinguish between two types of dependents: packages distributed via the package manager, and external GitHub projects depending on npm packages. We observe that the number of vulnerabilities in npm is increasing and being disclosed faster than vulnerabilities in RubyGems. For both package distributions, the time required to disclose vulnerabilities is increasing over time. Vulnerabilities in npm packages affect a median of 30 package releases, while this is 59 releases in RubyGems packages. A large proportion of external GitHub projects is exposed to vulnerabilities coming from direct or indirect dependencies. 33% and 40% of dependency vulnerabilities to which projects and packages are exposed, respectively, have their fixes in more recent releases within the same major release range of the used dependency. Our findings reveal that more effort is needed to better secure open source package distributions.